IGIP and the of engineering education in Russia and in the world - Vjacheslav M. Prikhodko; A. N. Solovyev (Высшее образование в России)
The paper presents the basic directions of modernization IGIP curriculum for training and professional development of teachers of engineering universities, which were approved at a meeting of the Executive Committee of the International Society for Engineering Education IGIP March 13,2013. We comment this modernization from the point of view of the global state of engineering education, and the features of using the updated plan in parallel with modernization of higher education in Russia.